Characterizing candidate decompression rates for hypobaric hypoxic stunning of pigs. Part 2: Pathological consequences - Baxter, Emma M.; McKeegan, Dorothy E. F.; Farish, Marianne; Thomson, Jill R.; Clutton, Richard E.; Greenhalgh, Stephen N.; Gregson, Rachael; Martin, Jessica E. (Frontiers in Veterinary Science, 2022)
Pigs are commonly stunned pre-slaughter by exposure to carbon dioxide (CO2), but this approach is associated with significant welfare concerns. Hypobaric hypoxia, achieved with gradual decompression (also known as Low Atmospheric Pressure Stunning or LAPS) may be an alternative, allowing the retention of welfare friendly handling approaches and group stunning. Although validated in poultry, the feasibility and welfare consequences of gradual decompression for pigs are unknown. Here, we characterize pathological changes in pigs resulting from exposure to a range of candidate decompression curves (ranging from 40-100ms-1 ascent equivalent, with two cycle durations 480s and 720s). To protect welfare, we worked on unconscious, terminally anesthetized pigs which were subject to detailed post-mortem examinations by a specialized porcine veterinary pathologist. All pigs were killed as a result of exposure to decompression, irrespective of cycle rate or length. Pigs showed no external injuries during ante-mortem inspections. Exposing pigs to decompression and the unavoidable subsequent recompression resulted in widespread congestion in the ears, oral cavity, eyes, orifices, nose, frontal sinus, nasal turbinates, calvarium, brain, trachea, stifle, liver, spleen, heart, lungs, abdomen, intestines, colon, kidney and stomach. Various severities of hemorrhage were observed in the kidneys, posterior and anterior thoracic, left and right lungs, spleen, liver, stifle, orifices, legs, tracheal lumen, brain, calvarium and bony trabeculae, nasal turbinates, frontal sinus, sclera and eyes. In general, faster decompression rates produced higher scores, but in the eyes, sclera and kidneys, faster decompression rates were associated with marginally lower congestion scores. There was considerable individual variation in pathological scores across all body regions. The congestion and haemorrhage observed could translate into welfare harms in conscious pigs undergoing this type of stunning, depending when in the cycle the damage is occurring, but no welfare related conclusions can be drawn from the responses of unconscious pigs. Since recompression is always required, its effects cannot be separated from decompression. This study represents the first systematic attempt to identify candidate rate profiles to underpin future explorations of decompression as a stunning method for pigs. These pathological findings also inform discussions about the likely carcass quality implications of this novel stunning method.